Scoping review on socioemotional skills in the prevention of suicidal behavior among adolescents - Joviana Quintes Avanci; Aline Ferreira Gonçalves; Orli Carvalho da Silva Filho; Pedro Henrique Tavares; Simone Gonçalves de Assis (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: Promoting socioemotional skills has been highlighted among the evidence to prevent suicidal behavior in childhood and adolescence. This review aimed to map and analyze national and international scientific papers on initiatives and programs for the prevention of suicidal behavior in adolescence based on the theoretical framework of socioemotional skills. It is a scoping review using the methodology proposed by the Joanna Briggs Institute. Eleven academic bibliographic databases were analyzed, and searches were conducted on institutional websites related to suicide prevention and Google. Papers in Portuguese, Spanish, French, and English from 2010 to July 2022 were included in the review, which consisted of 97 studies, analyzed through data matrix and thematic grouping. The results show that most are international and focused on suicide, not on self-harm alone. In general, they have an informational and instructional bias for professionals, institutions, and governments, proposed laws, programs and action plans, studies on the role of socioemotional skills and intervention research. Few strategies have been clearly tested and validated. The key elements are the ability to perceive, recognize, understand, express, and regulate one's own emotions, get motivated, and build empathy in relationships. Schools are key players in this process and the health system should act as a collaborative network. National and local prevention plans are required, emphasizing the role of schools, the health sector, and intersectoral coordination to promote health and quality of life.